Angelica sinensis polysaccharide as potential protectants against recurrent spontaneous abortion: focus on autophagy regulation - Yeli Sun; Guohua Li; Mengwen Kong; Junyuan Li; Shuyun Wang; Yuan Tan (Frontiers in Medicine)
IntroductionRecurrent spontaneous abortion (RSA) represents a significant clinical challenge, with its underlying mechanisms yet to be fully elucidated. Despite advances in understanding, the precise pathophysiology driving RSA remains unclear. Angelica sinensis, a traditional herbal remedy, is frequently used as an adjunctive treatment for miscarriage. However, it remains uncertain whether its primary active component, Angelica sinensis polysaccharide (ASP), plays a definitive role in its therapeutic effects. The specific function and mechanism of ASP in the context of RSA require further investigation.MethodsIn this study, we sought to evaluate autophagy levels at the maternal-fetal interface in RSA patients and in an RSA mouse model treated with ASP, complemented by a comprehensive metabolomic analysis. Autophagy flux in the decidua was compared between eight RSA patients and eight healthy pregnant women. Additionally, changes in autophagy flux were assessed in an RSA mouse model following ASP treatment, with embryos and placental tissues collected for subsequent metabolomic profiling.ResultsOur results revealed a significant reduction in Beclin 1 protein levels in the decidua of RSA patients compared to the normal pregnancy group. Conversely, ASP treatment in the RSA mouse model restored autophagy-related protein expression, including ATG7, ATG16L, and Beclin 1, to levels higher than those observed in the untreated RSA group. Metabolomic analyses further identified significant changes in phosphatidylethanolamine levels between ASP-treated and control groups, with differential metabolites enriched in pathways related to glycolysis/gluconeogenesis, glycerolipid metabolism, and glycine, serine, and threonine metabolism. Functional assays revealed that ASP enhances trophoblast cell proliferation, migration, and invasion.ConclusionIn summary, our findings demonstrate diminished autophagy activity in RSA patients, while ASP appears to restore autophagy and regulate key metabolic pathways, including glycolysis/gluconeogenesis. These results provide new insights into the protective mechanisms of ASP in RSA, suggesting its potential as a therapeutic intervention for this condition.